Poder em Hannah Arendt: uma leitura - Manzato, Marcos Valério Carvalho (2007)
It is reasonable believing that the idea of power construction produced by Hannah Arendt and registered in the philosophy and politics circles, that it is taking up spaces in different moments, has her personal experiences as inspiration. The intellectual trajectory of the writer has begun in philosophy, next to important germane characters and philosophers, in special Martin Heidegger and Karl Jaspers, leaving after for the politics theory by the influence of Henrich Blücher, in the United States of America, and has gotten back, at last, for the philosophy. It is possible grasping in the Arendt s thought tries to show a meaning of politics that develops itself inside of a conception of world and with the men, included in their various human activities and that had divided in 1. labor that activity said by needy and at the same time, trivial inside a biological process, that it is derived, once that it consumes in its own metabolism individual or collective; 2. the work by it and its extraction done from nature of the things are created by the homo faber, with its consequent world conversion in a space of shared objects by the human being; and the 3. action the only activity that fulfills directly among the men without the objects or the material mediation. The action occupies, at the arendtian context, one of the fundamental conditions in the man s life, united by the capacity of leading free his own destiny, represented still the only way of individual expression. Arendt searches to show a power conception that it is not limited from domination or hierarchies aspects, but free from those situations of pure submission, subordination or leadership circumstances by the men. The power for Arendt is built by the interactions of three elements, in other words, 1. the whole action, 2. the communication and the 3. common sense. Arendt, with her thought about power, includes every mechanism of whole action function, which becomes one of the biggest collaborators in the democratic process, serving as incentive for communities and organizations in their fights or demands for rights that can take to formation and development of specific ideas, including the direct and continuous participation. Nevertheless, there are difficulties for introducing the participating democracy, mainly in the under-developing countries. In Brazil, there is a way in this point, by some mechanisms contained in the Federal Constitution of 1988. This is the point of this investigation